Cytotoxicity of aqueous cigarette smoke extract is affected by properties of pipettes used to prepare the extract - Bernstein, Eric D (Matters (Zur), 2019)
Cigarette smoke contains a host of molecules including toxins and carcinogens, most of which have not been well studied. Aqueous cigarette smoke extract (CSE) is one of various cigarette smoke derivatives that can be used for in vitro studies, and the influence of different method parameters on CSE composition and toxicity remains incompletely understood. Herein, we prepared CSE by bubbling cigarette smoke through mammalian cell culture medium, varying the type of pipette inserted into the recipient medium. Changing this one component of the preparation apparatus had a marked effect on the toxicity of the resulting CSE. Since many other parameters can also be varied in CSE preparation, these results stress the importance of standardization within and between studies.